2012
DOI: 10.5505/tjtes.2012.98511
|View full text |Cite
|
Sign up to set email alerts
|

Early period psychiatric disorders following burn trauma and the importance of surgical factors in the etiology

Abstract: AMAÇYanık travması sonrasında erken dönemde ortaya çıkan psikiyatrik bozukluklar değerlendirildi. GEREÇ VE YÖNTEMYanık travmasına maruz kalan 1369 hastanın dosyası geriye dönük olarak incelendi. Psikiyatrik bozukluk saptanan 45 hasta yaş, cinsiyet, kronik hastalık, yanık öncesindeki psikiyatrik bozukluk, yanık nedeni, yanık yüzdesi, yanık derecesi, ek travma, ameliyat sayısı, hastanede kalış süresi, ekstremite amputasyonu, entübasyon durumu, psikiyatrik semptomlar, travma sonrası psikiyatrik bozukluk ve mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…The current literature shows a delirium prevalence of 29% and 77% in adults admitted to a burn ICU. 11,12 At two specialized burn centers, delirium was diagnosed in 16% and 39% of the admitted adults. 13,14 Risk factors for delirium have been widely investigated for surgical and nonsurgical populations, but not for burn center patients.…”
mentioning
confidence: 99%
“…The current literature shows a delirium prevalence of 29% and 77% in adults admitted to a burn ICU. 11,12 At two specialized burn centers, delirium was diagnosed in 16% and 39% of the admitted adults. 13,14 Risk factors for delirium have been widely investigated for surgical and nonsurgical populations, but not for burn center patients.…”
mentioning
confidence: 99%
“…Similar to our results, anxiety disorder was defined in 14% and acute stress disorder in 5.8% of their patients (26) . Yabanoğlu et al (2012) reviewed the files of 1369 cases, and reported that the rate of psychiatric diagnosis within 15 days after the burn incident was 3.2%, and the diagnoses were PTSD in 26.6%, delirium in 24.4%, anxiety disorder in 17.7%, depression in 15.5% of the patients, respectively (22) . In our study, we observed that 33 patients (19%) died during the four-year period and the majority of this group was diagnosed as delirium (n=14, 42.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Turkey examining burns and mental disorders were reviewed, and a study analyzing family characteristics of children and adolescents with corrosive burns and another study evaluating burn related psychiatric disorders in children were identified (20,21) . There was only one study examining psychiatric disorders in the early period in an adult population (22) . Therefore, our study will contribute to the literature in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Post travmatik stres bozukluğu, anksiyete ve depresyon yanık hastalarının sıklıkla karşılaştıkları sorunlardır (16). Hastanın izlendiği günler içinde bilinci açık ve koopereydi, kendisini tam olarak ifade edebildiği gözlendi.…”
Section: Psikolojik Bakım Ve Destekunclassified
“…Özellikle kadınların yanık sonrası beden imajı ile ilgili daha çok sorun yaşadığı, (16)(17)(18)(19) özellikle yüzdeki yanıkların depresyon için tetikleyici olduğu, yanık yüzdesi ve yanan vücut bölgesinin psikiyatrik semptomlara yol açtığı öngörülmektedir (16)(17)(18)(19)(20). Hastanede kaldığı süre içinde 8 kez greftleme yapılan olgunun durumu kabullenmesi zaman aldı.…”
Section: Cinselliğin Ifadesiunclassified